Fifty Years of Bangladesh Parliament : A Critical Evaluation - Chowdhury, M. Jashim, (Brill's Asian Law Series ;, 2025)
This book critically examines the constitutional position and contribution of the Bangladesh Parliament during the fifty years of its existence. Examining the institution through a "Westminster" lens, the book unearths how and why it behaves in an (un)Westminster, rather say the "Eastminster", way. This book is the first of its kind attempting a separation of powers and checks and balances inspired analysis of the Parliament vis-à-vis Bangladesh's government, judiciary, and the people. It explains how its internal democracy deficit arising from the country's undemocratic political partises deny the Bangladesh Parliament, its rightful place within the country's constitutional design.